2016
DOI: 10.1175/jhm-d-15-0126.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Partitioning of Turbulent Fluxes at Urban Sites with Varying Vegetation Cover

Abstract: 21 36 37 Key Words: Bowen ratio, irrigation, JULES, land surface model, spin-up strategy, urban vegetation 38 39 40National University urban canopy model (Ryu et al., 2011). Typically these models are designed to 47 represent the energy balance of the various facets that make up an idealized urban canopy. Often 48 this idealized urban canopy is treated as a symmetric street canyon geometry with varying degrees 49 of complexity, ranging from a bulk canyon (e.g., Best, 2005), separate roof, walls and road, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…The improvement was physically grounded in the strong sensitivity of summer temperature variability to local urban effects and land-use properties, which were better represented in the high-resolution SURFEX-TEB simulations when compared with the coarseresolution E20C. This sensitivity was systematically investigated, and urban built-fraction (fraction of surface covered by buildings or roads), surface albedo and surface emissivity emerged as key parameters, in agreement with previous findings [7,15,21].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The improvement was physically grounded in the strong sensitivity of summer temperature variability to local urban effects and land-use properties, which were better represented in the high-resolution SURFEX-TEB simulations when compared with the coarseresolution E20C. This sensitivity was systematically investigated, and urban built-fraction (fraction of surface covered by buildings or roads), surface albedo and surface emissivity emerged as key parameters, in agreement with previous findings [7,15,21].…”
Section: Discussionsupporting
confidence: 80%
“…Urban canopy numerical models are a useful tool for studying and predicting temperature extremes over urban regions. This has been demonstrated by several previous studies focusing on different cities across the world, under different global warming scenarios, urban density growth scenarios, urban vegetation fractions, and human energy consumption scenarios [15][16][17][18][19]. However, accurate simulation of local urban effects requires very high-resolution (on order of a few kilometers or less) [20,21].…”
Section: Introductionmentioning
confidence: 95%
“…Intraurban studies have been conducted in European cities (Christen & Voogt, 2004;Offerle et al, 2006) to explore energy partitioning and the surface energy balance (SEB), with an emphasis on comparing across different urban land covers and to nearby rural areas. Nevertheless, few studies have observed the effects of different types of urban land covers on the SEB in arid and semiarid environments and the partitioning of turbulent fluxes in a comparative manner such that the effects of precipitation and outdoor water use can be discerned (e.g., Best & Grimmond, 2016;Coutts et al, 2007;Liang et al, 2017). grass) and xeric (drip irrigated trees with gravel cover) landscaping (e.g., Song & Wang, 2015;Volo et al, 2014;Yang & Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, reanalysis products have been little used in the modelling of urban water and energy exchanges. As the WATCH WFDEI reanalysis data (Weedon et al 2011(Weedon et al , 2014 are specifically derived for hydrological modelling from ERA-Interim, and have been used to model surface energy fluxes in 20 different urban areas (Best and Grimmond 2016), they are chosen for this study.…”
Section: Introductionmentioning
confidence: 99%